1998
DOI: 10.1071/rj9980177
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change in Queensland's Grazing Lands: Ii. An Assessment of the Impact on Animal Production From Native Pastures.

Abstract: The 160 million ha of grazing land in Queensland support approximately 10 million beef equivalents (9.8 million cattle and 10.7 million sheep) with treed and cleared native pastures as the major forage source. The complexity of these biophysical systems and their interaction with pasture and stock management, economic and social forces limits our ability to easily calculate the impact of climate change scenarios. We report the application of a systems approach in simulating the flow of plant dry matter and uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
3
37
0
2
Order By: Relevance
“…Similar results were obtained by Hall et al (1998) using simulation of beef cattle liveweight gain at three locations of Australia. The authors found that ± 10% change in rainfall was magnified to be ± 15% change in animal production (liveweight gain per ha), depending on location and temperature change, and climate change impacts on pasture capacity/risk varied considerably depending on moisture, temperature or soil nutrients.…”
Section: Resultssupporting
confidence: 73%
“…Similar results were obtained by Hall et al (1998) using simulation of beef cattle liveweight gain at three locations of Australia. The authors found that ± 10% change in rainfall was magnified to be ± 15% change in animal production (liveweight gain per ha), depending on location and temperature change, and climate change impacts on pasture capacity/risk varied considerably depending on moisture, temperature or soil nutrients.…”
Section: Resultssupporting
confidence: 73%
“…Regardless of the criterion chosen for optimisation (usually economics or profitability), all management decisions interact with climatic and other natural features of each dynamic system (Mayer et al 1998). The only realistic method of investigating these interactions is with simulation models that encompass the whole system, from rainfall and soils, to pasture production and animal intake (McKeon et al 1990;Hall et al 1998), herd dynamics, and through to the economics of animals turned off .…”
Section: Introductionmentioning
confidence: 99%
“…The changes in seasonal patterns of forage availability could pose additional challenges for grazing management in the rangeland. Similarly, the climates become hotter and drier; pasture composition is likely to shift to species that may be less suitable for grazing [14]. Climate change has observed to affect rangeland species richness and biodiversity.…”
Section: Climate Change Effect On Feed Availabilitymentioning
confidence: 99%